Evaluation of the microbiological quality and effect of washing in lettuce (Agroindustria, Sociedad y Ambiente, 2020)
Currently, the consumption of lettuce is a cause for concern regarding food safety and food safety, due to the possible presence of pathogenic microorganisms. The objective of the work was to evaluate the microbial quality and the effect of washing the lettuce with water, lemon juice solution and 5% vinegar at 0, 15 and 30 minute immersion of the treatments. Lettuces were purchased from 4 marketing units (A, B, C and D) in the city of Barquisimeto, Lara-Venezuela. The lettuces were selected visually free of damage, the sample was homogenized by size and divided into three batches of 36 lettuces per market, applying the treatments: washing in immersions in water (T1), lemon juice solution at pH 2, 5 (T2) and 5% vinegar solution at pH 2.8 (T3) at three washing times: 0, 15 and 30 minutes. A factorial design was used and the data was analyzed with the NCSS program. The total count of mesophilic aerobes, enterobacteriaceae, Escherichia coli expressed as CFU / g and the presence / absence of Pseudomonas were determined for each sample in triplicate. The presence of different microorganisms in the lettuce samples was verified. The ranges of the microbial load obtained allowed the lettuce samples marketed in markets A, B, and D of Barquisimeto to be classified at the level of acceptable microbiological quality and that of market C as unacceptable. Washing with water, lemon juice solution, and 5% vinegar solution significantly reduced the microbial load present in the lettuce samples. The highest efficiency was achieved with the use of lemon juice solution, obtaining 72% efficiency; For its part, the vinegar solution had an efficiency of 66% at 30 min.
Keywords: Lettuce; pathogens; safety; quality